GeoBioMed perspectives on kidney stone recurrence from the reactive surface area of SWL-derived particles - Lauren G. Todorov; Mayandi Sivaguru; Amy E. Krambeck; Matthew S. Lee; John C. Lieske; Bruce W. Fouke (Scientific Reports, 2022)
Abstract Shock wave lithotripsy (SWL) is an effective and commonly applied clinical treatment for human kidney stones. Yet the success of SWL is counterbalanced by the risk of retained fragments causing recurrent stone formation, which may require retreatment. This study has applied GeoBioMed experimental and analytical approaches to determine the size frequency distribution, fracture patterns, and reactive surface area of SWL-derived particles within the context of their original crystal growth structure (crystalline architecture) as revealed by confocal autofluorescence (CAF) and super-resolution autofluorescence (SRAF) microscopy. Multiple calcium oxalate (CaOx) stones were removed from a Mayo Clinic patient using standard percutaneous nephrolithotomy (PCNL) and shock pulse lithotripsy (SPL). This produced approximately 4–12 mm-diameter PCNL-derived fragments that were experimentally treated ex vivo with SWL to form hundreds of smaller particles. Fractures propagated through the crystalline architecture of PCNL-derived fragments in a variety of geometric orientations to form rectangular, pointed, concentrically spalled, and irregular SWL-derived particles. Size frequency distributions ranged from fine silt (4–8 μm) to very fine pebbles (2–4 mm), according to the Wentworth grain size scale, with a mean size of fine sand (125–250 μm). Importantly, these SWL-derived particles are smaller than the 3–4 mm-diameter detection limit of clinical computed tomography (CT) techniques and can be retained on internal kidney membrane surfaces. This creates clinically undetectable crystallization seed points with extremely high reactive surface areas, which dramatically enhance the multiple events of crystallization and dissolution (diagenetic phase transitions) that may lead to the high rates of CaOx kidney stone recurrence after SWL treatment.